THE INFLUENCE OF PROVIDING HEALTH EDUCATION IN BREASTFEEDING TECHNIQUES ON THE KNOWLEDGE OF PUBLIC WOMEN IN THE UPTD WORKING AREA OF THE MAJA MARGA PUNDUH COMMUNITY HEALTH CENTER IN 2024 - Amelia, Priska; Besmaya, Beniqna Maharani Besmaya; Putri, Nopi Anggista Putri; Sulistiawati, Yuni Sulistiawati (Universitas Aisyah Pringsewu, 2024)
Exclusive breastfeeding coverage in Pesawaran Regency in 2022 is 72.71%; in the Maja Public Health Center, the coverage of babies less than six months old who receive exclusive breastfeeding in 2023 is 69.8%, where this figure has not yet reached the expected target of 80%. The wrong method can cause sore nipples and suboptimal breast milk supply, so mothers are reluctant to breastfeed their babies and replace them with formula milk. Media used for health promotion, including audio-visual media, are considered better and more interesting because they contain heard and seen elements. The research objective is to determine the effect of providing health education using video media about breastfeeding techniques on the knowledge of postpartum mothers. This research method uses a pre-experimental design with a pre-test and post-test design approach. The research subjects were all postpartum mothers in the Maja Marga Punduh Public Health Center. The research object is knowledge about breastfeeding techniques, data collection using questionnaires and data analysis using the dependent t-test. The sample was 15 people. The research showed that the average knowledge before health education was 13.13 (sufficient). The average knowledge after being given health education is 20.2 (good). Providing health education on breastfeeding techniques affect the understanding of postpartum mothers in the Maja Marga Punduh Public Health Center in 2024 (p-value 0.000). Researchers suggest providing information about appropriate breastfeeding techniques that can be used as supporting material for program planning to increase the achievement of exclusive breastfeeding.